2014
DOI: 10.1016/j.jhealeco.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Retiree health insurance for public school employees: Does it affect retirement?

Abstract: Despite the widespread provision of retiree health insurance for public sector workers, little attention has been paid to its effects on employee retirement. This is in contrast to the large literature on health-insurance-induced “job-lock” in the private sector. I use the introduction of retiree health insurance for public school employees in combination with administrative data on their retirement to identify the effects of retiree health insurance. As expected, the availability of retiree health insurance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…84 .86 .88 .9 .92 2008 2009 2010 2011 2012 2013 2014 2015 2016 2017 2018 Full_time_if_worker . 1 .12 .14 .16 2008 2009 2010 2011 2012 2013 2014 2015 2016 2017 2018 Retired Source: CPS Basic monthly Individuals ages 50-64, Education_HS_or_less, not regression adjusted Trends in labor market outcomes by state Medicaid status Non-Expansion Expansion .66 .68 .7 .72 .74 200820092010201120122013201420152017 In_the_labor_force .1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…84 .86 .88 .9 .92 2008 2009 2010 2011 2012 2013 2014 2015 2016 2017 2018 Full_time_if_worker . 1 .12 .14 .16 2008 2009 2010 2011 2012 2013 2014 2015 2016 2017 2018 Retired Source: CPS Basic monthly Individuals ages 50-64, Education_HS_or_less, not regression adjusted Trends in labor market outcomes by state Medicaid status Non-Expansion Expansion .66 .68 .7 .72 .74 200820092010201120122013201420152017 In_the_labor_force .1…”
Section: Discussionmentioning
confidence: 99%
“…A large literature analyzes the effect of health insurance on the retirement decision (Blau & Gilleskie, 2001, 2006, 2008Fitzpatrick, 2014;French & Jones, 2011;Gruber & Madrian, 1995Gustman & Steinmeier, 1994;Johnson, Davidoff, & Perese, 2003;Karoly & Rogowski, 1994;Leiserson, 2013;Lumsdaine, Stock, & Wise, 1996;Madrian & Beaulieu, 1998;Madrian, Burtless, & Gruber, 1994;Nyce, Schieber, Shoven, Slavov, & Wise, 2013;Robinson & Clark, 2010;Rogowski & Karoly, 2000;Rust & Phelan, 1997;Scholz & Seshadri, 2013;Shoven & Slavov, 2014;Strumpf, 2010). Nearly all of these papers find that the availability of insurance that is not contingent upon one's own continued work -from Medicare, as a dependent on a spouse's policy, from coverage intended for early retirees, or from COBRA -significantly increases the probability of retirement.…”
Section: Background On Health Insurance and Retirementmentioning
confidence: 99%
“…A study by Boyle and Lahey (2010) found that individuals with access to veteran health insurance decreased work on both the extensive and intensive margins. Fitzpatrick (2013) found that the provision of retiree health insurance to Illinois public schoolteachers induces earlier retirement. Finally, Lin (2014) found that HIPAA regulations in the non-group health insurance market increase the retirement propensity by 1.2 to 1.5 percentage points.…”
Section: Literature Reviewmentioning
confidence: 99%
“…shown the effects of employer-provided RHI to increase the odds of early retirement by 20% to 30% (Shoven & Slavov, 2014;Nyce et al, 2013;Fitzpatrick, 2014) although they would be at the low end of the range of prior estimates.…”
Section: Discussionmentioning
confidence: 83%